Ruthenium half-sandwich complexes bound to protein kinase Pim-1. - Debreczeni, J; Bullock, A; Atilla, G; Williams, D; Bregman, H; Knapp, S; Meggers, E (2006)
(Figure Presented) Keeping in shape with half a sandwich: The structure of a picomolar organoruthenium inhibitor bound to the ATP-binding site of the protein kinase Pim-1 (see picture) demonstrates that the ruthenium center has solely a structural role in organizing the organic ligands in the three-dimensional receptor space, thus yielding a structure that is complementary in shape and functional group presentation to the active site of Pim-1. © 2006 Wiley-VCH Verlag GmbH and Co. KGaA.